ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEPSI PEMILIHAN KARIR SEBAGAI AKUNTAN PADA MAHASISWA PENDIDIKAN PROFESI AKUNTANSI ( PPAK ) UNIVERSITAS SAM RATULANGI - Rorong, Elisa Levina; Sondakh, Jullie J.; Wokas, Heince (Universitas Sam Ratulangi, 2013)
This research aims to know the influence of financial respect, professional training, professional recognition, social values, working environment, job market considerations and personality partially or together against the accountant career selection by students of University of Sam Ratulangi PPAkThe object of this research is the accounting profession education student University of Sam Ratulangi active registered as a student with a total population of 80 people. The data collected is classified as primary data which is obtained by questionnaires distribution. Data Processing is conducted by using Multiple Regression Analysis.The result of this research indicate that financial respect, profesional training, profesional recognation, social values, working environment, job market considerations and personality to career choice on Accounting either it is partially and simultaneously influence, but partially Accounting, while financial respect, professional training,Â social values, working environment and personality have the significantly influence on career choice of accounting. From the ANKOVA test there is a different factor influence accountant career selection by students who already work and not yet working Keyword : financial respect, professional training, professional recognition, social values, working environment, job market considerations, personality and Accounting Career.